Third-order relativistic dynamics: classical spinning particle travelling in a plane - Matsyuk, R. (Condensed Matter Physics, 1998)
Mathisson’s ‘new mechanics’ of a relativistic spinning particle is shown to
follow, in the case of planar motion, from only general requirements of relativistic
invariance and of the dependence on third order derivatives along
with the ‘variationality’ feature. The hamiltonian counterpart ultimately recovers
the Dixon equations for this case with the Pirani supplementary
condition. Показано, як ”нова механіка“ Матісона для опису частинки зі спіном випливає (у випадку вільного руху в одній площині) лише із загальних вимог про релятивістичну інваріянтність та суттєву залежність від похідних аж до третього порядку в такому рівнянні руху, яке випливає
з варіяційного принципу. Гамільтонів підхід тоді знову відтворює рівняння Діксона з доповняльною умовою Пірані.